THE IMPACT OF THE PANDEMIC ON HUMAN CAPITAL. HUMAN CAPITAL INDEX (Globalization and Business, 2023)
In the first half of 2020, as a result of the spread of coronavirus in the world and the implementation of preventive measures, the volume of production was sharply reduced, and there were shortages in the supply of goods the service sector was limited. Additional difficulties for Georgia and many other developing countries have been created by the sharp decline in remittances from our citizens in other countries, which has become one of the reasons for the decline in retail trade. Countries whose tourism accounts for a significant share of their economy have been particularly hard hit. In countries where restrictions were delayed, more massive pandemic outbreaks occurred, with high mortality rates and severely restricted business activities. As a result, unemployment and poverty rates have risen. After the "repulsion" of the first wave of the virus, in many countries, including ours, there was a certain revival of the economy. However, this increased mobility has led to an even more devastating second and subsequent waves of the virus and the world is currently fighting yet another wave. The pandemic factor in Georgia, in parallel with the second, third, and subsequent waves, was accompanied by an unstable political situation. This has become an additional pressure and impacted the economic downturn and the devaluation of the Georgian Lari.  As in the rest of the world, the coronavirus pandemic in Georgia has had a direct impact on human capital, with a negative impact on education and human health. Unlike natural disasters, the devastating effects of which on physical capital are far greater than on humans, the pandemic has left factories, plants, and infrastructure intact, but has had an extremely negative impact on human health, disrupting the learning process of pupils and students.  The closure of schools and colleges and the transition to distance learning have resulted in the loss of much of the school year. A separate problem is the less efficiency of the distance learning process and the difficulties associated with knowledge testing. At the same time, the current situation exacerbates the divergence between different social strata in terms of access to full-fledged education.  The pandemic kills thousands of people. Many of those who recovered from the pandemic suffer from both health and psychological problems. In the current situation, the health sector is not given the full opportunity to deal with other diseases. Once the pandemic is over, significant investments will need to be made in both education and healthcare.  The level of human capital development is an important factor for the economies of all countries. Differences between countries in GDP by 10-30% are caused by differences in the level of human capital development. It is noteworthy that the current shortcomings caused by the pandemic in the development of human capital will have a negative impact on many in the coming years.  Since 2018, the World Bank has been implementing the Human Capital Development Project. Within the framework of this project, a so-called Human Capital Index (HCI) was developed, which shows the productivity of the next generation of workers compared to the standard of complete education and perfect health. Due to the pandemic, this index has deteriorated in all countries of the world, including Georgia.